Marginacions d'ahir i d'avui:drets humans i discursos discriminatoris a la pel·lícula También la lluvia. - RIPA, VALENTINA (Scripta, 2020)
The present article analyses the film También la lluvia, a good example of how cinema «for the general public» can also contribute, through its representations, to people's awareness; in this case, on themes such as the indigenous genocide in the modern era, the historical marginalisation of the indigenous peoples of Latin America and the right to water that is questioned all over the word. Particularly noteworthy is the inherent racism of the discourses of the elites that are reproduced in the film and that are a good example -in the realistic code of También la lluvia- of rather widespread ideas and language.